Atenção ao pré-natal e ao puerpério: uma análise a partir do 1° e 2° ciclo de avaliação externa do Programa Nacional de Melhoria do Acesso e da Qualidade da Atenção Básica PMAQ AB - Silva, Geane (2019)
Prenatal care, with regard to women's health, is one of the most important strategies in promoting the health of the pregnant woman to identify and intervene according to the risk assessment. In order for health care to respond adequately to women's needs, it is essential to evaluate public health services, with emphasis on Primary Care, the responsibility to coordinate care and to be the main gateway to user to the Unified Health System (SUS). In view of this, the National Program for Improving Access and Quality of Primary Care (PMAQ-AB) has been highlighted as a strategy for evaluating AB. The purpose of this study is to evaluate prenatal and puerperal care, based on the first and second cycle of PMAQ-AB. This is a descriptive, cross-sectional and quantitative approach. The sample was composed of population bases, whose sample units are 17,202 basic health units for the first cycle; 29,778 basic health units for the second cycle of PMAQ-AB, throughout Brazil. Statistical software SPSS version 20.0 was used for the analysis of the data for both descriptive and inferential statistics. These results were presented in graphs and tables constructed with the aid of the Office Excel 2010 program. The results were presented in two articles format, first dealt with descriptive analysis and analysis based on the statistical model. The first article aimed to describe the characteristics of prenatal and puerperal care performed by EqESF in cycle I and cycle II, listing the main fragilities and potentialities when comparing the regions with each other; the second one had the objective of describing the characteristics of prenatal and puerperal care performed by EqESF in cycle I and cycle.